Acceleration of the weapon hand discriminates between elite and non-elite fencers - Mentz, L.; Weichenberger, M.; Hessling, M.; Liu, Y.; Steinacker, J. M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Fencing is influenced by physiological determinants such as speed, endurance and strength. Movement analysis of upper and lower limbs is useful to analyze performance in fencing. Especially velocity of the weapon hand is related to the level of the fencer. Due to theoretical and methodological reasons, it seems advantageous to measure acceleration of the weapon hand. However, it is not known if acceleration is also a characteristic of top level fencers. To this end, we analyzed if acceleration of the weapon hand distinguishes between elite and non-elite fencers. Methods: 31 male epée fencers of the German national team were examined. The group consisted of n = 18 international level (elite) and n =13 national level (non-elite) fencers. The elite fencers were further divided into three subgroups, according to their national qualification outcome. 16 infrared markers of a 3D-Motion-Capture-System (AS 300, Lukotronic/Steinbichler, Austria) were attached to important landmarks of the body. Two markers at the wrist and the dorsum of the weapon hand were of interest. The system recorded movements and calculated the velocity of the weapon hand. Three different attacks were analyzed, namely touch, lunge, and flèche. A custom-built fencing dummy with 10 target areas was used during the experiment. Each attempt was triggered randomly by an optical signal of the target area by a green light. Then the fencer had to attack the target area as explosively and quickly as possible. For each attack the subjects had five attempts. By mathematical differentiation of the markers` velocity data, the acceleration of the weapon hand was obtained. Data was smoothed using a moving average filter. Results: Elite fencers showed a significantly higher acceleration of the weapon hand then non-elite fencers in all three attack modes (p < 0.001). There was no significant difference between the three subgroups of elite fencers. The flèche proved to be the movement with highest acceleration values throughout all groups. These values were significantly higher than those of the lunge and slightly higher than the touch. Discussion: The results demonstrate that acceleration of the weapon hand distinguishes elite from non-elite fencers. This is a relevant result, because acceleration is easier to be measured than velocity and is furthermore a better indicator for explosiveness and initial speed. Since acceleration of the weapon hand was not related to performance within the elite group, it remains unclear if improvements in acceleration above a certain threshold will help to improve performance. Conclusion We conclude that acceleration of the weapon hand is a determinant of fencing performance. Since it is easily to be measured, it has potential to become a part of routine performance analysis.